Affecting Employee Performance (Case Study at PT NIS ELINA SECTION - Semarang Branch) - Bodroastuti, Tri; Ginanjar, Retno; Nadia, Nicken (BIMA Journal (Business, Management, & Accounting Journal), 2024)
Purpose: This study examines factors affecting the performance of sales employees at PT NIS in Semarang. Methodology: The research involved 50 employees, using secondary data from questionnaires distributed via Google Forms. Multiple linear regression analysis was used for data analysis. Results: Communication (X1), Competence (X2), and System/Procedure (X5) positively and significantly affect employee performance (Y). Motivation (X3), Compensation (X4), Leadership (X6), and Corporate Culture and Environment (X7) do not have a significant impact. Findings: Communication, Competence, and System/Procedure are crucial for enhancing employee performance, explaining 80.4% of the performance variance. The remaining 19.6% is influenced by other factors not included in the study. Novelty: This study identifies key determinants of sales employee performance in the context of a specific company, providing insights for targeted improvements.Originality: The research offers a detailed analysis of various factors influencing employee performance using a comprehensive statistical approach. Conclusions: Effective communication, competence, and systematic procedures are essential for improving sales employee performance at PT NIS. Type of Paper: Research Paper